2017
DOI: 10.1128/iai.00252-17
|View full text |Cite
|
Sign up to set email alerts
|

AtlA Mediates Extracellular DNA Release, Which Contributes to Streptococcus mutans Biofilm Formation in an Experimental Rat Model of Infective Endocarditis

Abstract: Host factors, such as platelets, have been shown to enhance biofilm formation by oral commensal streptococci, inducing infective endocarditis (IE), but how bacterial components contribute to biofilm formation is still not clear. We demonstrated previously that an isogenic mutant strain of deficient in autolysin AtlA (Δ) showed a reduced ability to cause vegetation in a rat model of bacterial endocarditis. However, the role of AtlA in bacterial biofilm formation is unclear. In this study, confocal laser scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…However, the survival rate of the VicK-deficient strain was found to be enhanced at low pH due to improved resistance to autolysis (Senadheera et al, 2009). VicK was later found to be responsible for calcium ion sensing and subsequent AtlA-mediated autolysis (Jung et al, 2017). The ComDE TCS, comprised of ComD histidine kinase and ComE response regulator, is a vital component of quorum sensing mechanisms, which senses competence-stimulating peptides (CSPs) (Havarstein et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the survival rate of the VicK-deficient strain was found to be enhanced at low pH due to improved resistance to autolysis (Senadheera et al, 2009). VicK was later found to be responsible for calcium ion sensing and subsequent AtlA-mediated autolysis (Jung et al, 2017). The ComDE TCS, comprised of ComD histidine kinase and ComE response regulator, is a vital component of quorum sensing mechanisms, which senses competence-stimulating peptides (CSPs) (Havarstein et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The eDNA level in the matrix of biofilms was detected by PCR with specific primers for the 16S rRNA gene (Table 1) (Jung et al, 2017). S. mutans UA159 (5 × 10 6 CFU/mL in CDMS) was grown in tubes (200 μL; Axygen, Tewksbury, MA, United States) with TF3 (1/4 or 1/2× MIC) for 6 or 24 h; 0.0625% ethanol was used for the control groups, and sterile water was used for the blank groups.…”
Section: Methodsmentioning
confidence: 99%
“…Our results indicate that bacterial chaining is a caveat to the interpretation of in vitro biofilm assays for GAS, and possibly other streptococcal species, that could lead to missed or misinterpreted phenotypes. Autolytic activity has been positively correlated with the ability to form biofilms in vitro for S. pneumoniae, S. gordonii and S. mutans (25-27), but the direct role of chaining in inhibiting streptococcal biofilm formation has been unclear as some long-chaining strains also form biofilms (25). We showed that the effect of chaining on biofilm formation may not be easy to detect in the classical CV assays and is strongly dependent on handling (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuation in the virulence of E. faecalis Δ atlA in a zebrafish model of infection has been directly attributed to long-chain formation (24). Similarly, the autolysin LytB and its homologues have been identified in other streptococci, including S. pneumoniae, S. gordonii and S. mutans , as regulators of chain length, and deletion of the autolysin gene often decreased their capacity to form biofilms (25-27). Chaining induced by choline supplementation had been shown to inhibit S. pneumoniae biofilm formation, but the exclusive and mechanistic role of chaining in streptococcal biofilm formation has remained a topic for speculation (25).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of this organism to form a biofilm, as part of its colonization strategy in the mouth, relies both on its ability to synthesize adhesive glucans from sucrose and to induce the release of extracellular DNA (Ge et al, 2008;Zhu et al, 2018), which plays an important role in biofilm formation on the surfaces of teeth. In contrast, cardiac vegetations formed by colonization of the endothelium are expected to be composed of human platelets, fibrin and bacteria (Jung et al, 2012;Mancini et al, 2016), though glucans and extracellular DNA have also been reported to retain their importance in this environment (Jung et al, 2015(Jung et al, , 2017. To form this specialized platelet-containing biofilm S. sanguinis must express virulence factors that function within the context of heart tissue colonization and growth.…”
Section: Introductionmentioning
confidence: 99%